The comparative value of corn, open-pollinated grain sorghum, and hybrid grain sorghum as fattening feeds to fall pigs in the dry-lot. - Aubel, C.E. (Kansas Agricultural Experiment Station, 2011)
Five lots of pigs were self-fed free-choice in dry-lot. All lots received a mixed animal and plant protein supplement of 4 parts tankage, 4 parts soybean meal, 1 part linseed meal, and 1 part alfalfa meal. The open-pollinated sorghum was the Plainsman variety, of excellent quality, -being especially high in protein. The hybrid sorghum was Farmer's Union 222 and was somewhat high in moisture.
Keywords: Swine; Corn; Grain sorghum; Dry-lot